(untitled) (Research, Society and Development, 2025)
Toxoplasmosis is a medically significant zoonosis caused by the parasite Toxoplasma gondii, which causes congenital anomalies in the fetus. The risks of the disease go beyond fetal complications, as it impacts maternal health, causing mild to severe symptoms in pregnant women, requiring specialized monitoring to prevent future complications. Therefore, the objective of this study was to analyze the prevalence of gestational toxoplasmosis cases in the state of Paraná from 2019 to 2024. This is a retrospective, cross-sectional study with a quantitative approach, using data extracted from the Department of Information Technology of the Unified Health System (DATASUS). Between 2019 and 2024, the state of Paraná reported approximately 5,020 cases of gestational toxoplasmosis, with a significant increase in confirmed cases over the years. The highest incidence of cases occurred among pregnant women aged 20 to 39 years and with low levels of education. This pattern highlights the urgent need for integrated prevention strategies, strengthening prenatal care, and expanding access to information and healthcare.